Features of the Development of Emotional Intelligence in Adolescence - Dubrovynsky, Heorhii; Dudkevych, Mariana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article presents the results of a study of the peculiarities of the restructuring of the emotional sphere and behavior of adolescents. To characterize all the contradictions of the image of the "I" of the adolescent, it is not enough to explain only hormonal and physiological changes.The difficulty of moving to a new age may increase the stress of teenagers, so emotional intelligence development and related social factors are important for the formation of personality. Adolescence (14-17 years) is characterized by impulsiveness, the desire to insist on their own, and immaturity of their judgments. There is a concern for their physical attractiveness. The teenager becomes shy, which gives rise to insecurity and leads to behavior that tends to risk and social conflict. Many teenagers conclude that no one understands them. Violation of emotional intelligence in adolescents causes issues such as increased anxiety, problems of self-expression, communication, understanding, and breach of the regulation of their behavior, etc. Our study shows the ability to realizing the fact that the development of emotional intelligence (EI) is almost minimal. The reasons for this phenomenon allow us to look for opportunities to influence a situation and identify ways to overcome the crisis in the future.At the age of 14-17, teenagers strive to take a social position that meets their needs for self-determination, to show their abilities in many spheres of life. It is necessary to promote socially significant activities in adolescence. Properly organized classes at schools or lyceums for adolescents involves reaching a new level of motivation, implementation of the system "I and society", deployment of various forms of communication with adults based on moral cooperation.
Keywords: adolescence; emotional intelligence; self-expression